Mycorrhiza formation on olive varieties (Olea europaea L.) fit for cultivation in the state of Minas Gerais - Melloni, Rogerio (2020)
The olive tree, due to the high demand for the products olive and oil, is a relevant crop for the global food market. To improve its cultivation, increasing efforts have been invested in studies on biological factors of the soil-plant relationships, mainly with regard to the exploitation of microorganisms such as arbuscular mycorrhizal fungi (AMF). In Brazil however, further research is still needed, both under controlled and field conditions. In this sense, this study investigated the formation of extraradical mycelium and spore numbers and diversity of mycorrhiza, on 17 olive tree (Olea europaea L.) varieties. These varieties, considered promising for cultivation in the state of Minas Gerais, are maintained in the olive germplasm bank of the Agricultural Research Institute of Minas Gerais (EPAMIG), at the Experimental Farm Maria da Fé. The response of the olive varieties differed in terms of the level of extraradical mycelium and mycorrhiza formation, since root colonization in the field varied from 0.4% to 3.6%. Under the edaphoclimatic conditions of the study region, no influence of the olive tree varieties on the total number of spores and diversity of AMF was detected, among which the fungal species Glomus ambisporum and Acaulospora scrobiculata were identified most frequently on the roots of the analyzed olive trees.